Evening Primrose Oil (Oenothera biennis L.) in Women’s Health: A Narrative Review of Clinical Evidence - Skłodowski, Tomasz; Wojciechowska, Karolina; Warych, Wiktor; Choroszewska, Ewelina; Baran, Julia; Bullmann, Agnieszka; Woroniecka, Katarzyna (Quality in Sport, 2026)
Evening primrose oil (EPO), derived from the seeds of Oenothera biennis L., has been widely used as a complementary therapeutic agent in various female health conditions. Its biological activity is primarily attributed to its high content of essential omega-6 fatty acids, particularly linoleic acid and γ-linolenic acid, which serve as precursors of anti-inflammatory prostaglandins. Over recent decades, increasing clinical interest has focused on the potential role of EPO in the management of premenstrual syndrome, mastalgia, menopausal symptoms, polycystic ovary syndrome, and other inflammatory or hormone-related disorders affecting women. The present narrative review aims to summarize current evidence regarding the phytochemical composition, proposed mechanisms of action, clinical efficacy, and safety profile of evening primrose oil in women’s health. A comprehensive literature search of electronic databases was conducted, including randomized controlled trials, systematic reviews, meta-analyses, and observational studies. Available evidence suggests that evening primrose oil may provide symptomatic relief in selected conditions, particularly mastalgia and certain menopausal symptoms, while results in premenstrual syndrome and other indications remain inconsistent. Overall, EPO appears to be well tolerated, although its therapeutic effectiveness varies depending on dosage, duration of use, and clinical indication. Further large-scale, well-designed clinical trials are required to establish clear recommendations for its use in general medical practice.